Strategi Pendisiplinan Anak Usia Dini Pada Program Kelas Kelinci di Yogyakarta (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
Basically a growing and developing child is unruly and difficult to understand the commands of the parents. This research uses descriptive qualitative methods, as well as by taking data by documentation, interviews, and observations. The results of the study showed that the strategies used in early childhood discipline at the BIAS Institute for the rabbit class program used learning strategies Learning By Doing, Fun Learning, Small Group, Habit Forming / Habituation, Humanist, Scientific Learning